Indicators of gendered control over agricultural resources: a guide for agricultural policy and research - Rao, Smriti (CGIAR Gender and Agriculture Research Network, 2016)
Although the importance of women’s contribution to the agricultural sector in developing countries is now widely acknowledged, there is little systematic evidence on how gender gaps in control over resources have changed over time in response to agricultural policy and technological interventions. In particular, few large-scale, national-level studies examine these effects for developing countries. This is surprising in light of the pervasive impact of agricultural technology and policy innovation on gender differences in control over productive resources for agriculture. Women are farmers and agricultural laborers in every part of the world. They are often responsible for the storage and processing of agricultural products. In some parts of the world, they play a key role in marketing crops. In almost all contexts, they play a central role in ensuring household food security, a goal that in turn affects crop choice and other agricultural decisions. Thus, every agricultural intervention is likely to impact women and, depending on the particular context of gender relations, impact them differently from men (Meinzen-Dick et al 2011).